THE POLICY AND CHARITY MODERNIZATION PROCESSES IN THE STAVROPOL REGION AT THE END OF XIX THE BEGINNING OF XX CENTURIES: THE EXPERIENCE OF SOCIAL AND POLITICAL RECONSTRUCTION - Tatyana Aleksandrovna Shebzukhova (Современная наука и инновации, 2022)
This article presents an analysis of the charity policy and modernization processes in the Stavropol region in the pre-revolutionary period. The author examines the specific features of forms of social care in the Stavropol region, the participation of representatives of national communities and different religious denominations in the resolution of social assistance